Perilaku Guru Dalam Mengiplementasikan Nilai-Nilai Spiritual Untuk Mewujudkan Pendidikan Efektif - Marno, Marno (J-PAI: Jurnal Pendidikan Agama Islam, 2015)
Islamic educational institutions still face a fundamental problem of which is related to the quality and quantity of teachers, has been done activities of education and training but those activities cannot solve that problems because the material of training oriented to development of hard skill,whereas fundamental problem human resources is related with lack of soft skill. Teacher’s behavior based on motivation and encouragement of high spirit because they have a concept that being teacher is a noble task. One of task of teacher is teach students to understand their God andtheir tasks in this world, make smart and personality student, education understood as an effective way to establish Allah’s religion and develop this country, education will determine the future of mankind and nation. The behavior of teacher in teaching task performed by spirit to teach and educate, love the profession and able to share their love and affection to their students able to create effective situation of learning. Teacher behavior shows the ability of personal and social religious, and professional competencies that impact to their way as effective teacher.Keyword: Teacher’s behavior Spiritual values, effective education